A brief review on the mental health for select elements of the built environment. Issue 2 (February 2021) - Beemer, Cody J.; Stearns-Yoder, Kelly A.; Schuldt, Steven J.; Kinney, Kerry A.; Lowry, Christopher A.; Postolache, Teodor T.; Brenner, Lisa A.; Hoisington, Andrew J.
Global urbanization, combined with evidence of increased prevalence of mental illness in urban environments, highlights a need to investigate potential connections between the built environment and mental health. Previous research has shown that the built environment may impact occupant mental health through its effects on connection to nature, personal control and indoor air quality. Contact with the natural environment has physiological and psychological benefits; consequently, reduced contact or exposure leads to negative mental health outcomes. The control an occupant has in the built environment can alter the mental health of individuals through direct pathways, such as prevention of exposures to environmental stressors and indirect pathways, such as social connections to others. Indoor air quality is connected to the mental health of built environment occupants, as particulate matter, malodorous irritants and toxins have all been shown to alter mental well-being. Opportunities for architects and engineers to optimize building designs that improve occupant mental health include planned urban greenspace, personalized temperature control and building ventilation. To understand optimization targets, interdisciplinary research utilizing controlled experiments are needed to confirm causality and improve our current understanding of mechanisms underlying the association between the built environment and mental health.